Find the average rate of change of the function f(x) = (-x^3) + 1: (a) From 0 to 2 (b) 1 to 3
Follow Math Help Forum on Facebook and Google+
Originally Posted by magentarita Find the average rate of change of the function f(x) = (-x^3) + 1: (a) From 0 to 2 (b) 1 to 3 the average rate of change for a function between and , for is given by
Are you saying to plug the values given into the function? Can you further explain your first reply? Thanks
Originally Posted by magentarita Find the average rate of change of the function f(x) = (-x^3) + 1: (a) From 0 to 2 (b) 1 to 3 let me do (a) f(x) = (-x^3) + 1 f(0)=(0)^3+1=1 f(2)=(-2)^3+1=-7 so average rate of change will be (f(2)-f(0))/2-0 -8/2=-4
I totally get it now. Thanks a million! It's easier than the textbook's explanation.
View Tag Cloud